Construction and Validation of Research Satisfaction Scale (RSS) for Post-Research Analysis of Graduates - Velamuri, Anusha; Mallappa, Vinaya Kumar Hebsale; Parikh, Neha (Indian Journal of Extension Education, 2024)
A better understanding of the researcher’s attitude starts with knowing their satisfaction level, which helps the agricultural universities understand research graduates and make necessary improvement plans. Absence of such a specific scale, forced to draft present piece in 2022 focusing on developing the Research Satisfaction Scale using the scale product method. Initially, 63 items were pooled, scrutinized, and reduced to 57 based on the rules of Edward and Kilpatrick and segregated into three groups as: ‘Before, while performing, and after performing research.’ Scale and Quartile values were calculated, and the statements with an S-value less than the Q-value were eliminated, bringing the number of statements to 53. For validation – Content Validity Index (CVI), both item and scale were used and Cronbach’s alpha for measuring reliability. The score of Item- CVI
Keywords: Content validity index; Cronbach’s alpha; Graduates; Research satisfaction; Scale development and scale product method